Epidemiological Mapping of Canine Angiostrongylosis in Portugal: Findings from a Nationwide Prevalence Survey - Beatriz Leal-Sousa; Joana Esteves-Guimarães; Jorge Isidoro Matos; Pedro Oliveira; Luís Lobo; Ana Cristina Silvestre-Ferreira; Carla S. Soares; Elena Carretón; Rodrigo Morchón; Ana Patrícia Fontes-Sousa; José Alberto Montoya-Alonso (Veterinary Sciences, 2025)
Considering the global health concern and the significant morbidity associated with canine angiostrongylosis, this study aimed to update the epidemiological profile and geographic distribution of the disease in canine populations across all continental and insular districts of Portugal, some of which were never studied before. A total of 1059 dogs were included in the study and tested for Angiostrongylus vasorum antigens using a commercial immunochromatographic assay. The overall prevalence was 1.13%. Higher infection rates were found in northern (3.9% in Viana do Castelo) and central (3.6% in Viseu and 3.8% in Lisbon) districts, and infection was reported, for the first time, in the districts of Leiria and Beja. The mild temperatures and elevated humidity levels, characteristic of Portugal’s northern and coastal regions, promote increased gastropod host activity and population density while also accelerating parasite development. The effect of wildlife reservoirs must also be considered, since higher seroprevalences were detected recently in red foxes from Portuguese northern regions. Bivariate Chi-square test analysis identified male sex and an outdoors lifestyle as risk factors. These findings confirm the enzootic presence of A. vasorum throughout the country and highlight the need for increased clinical awareness, routine screening, and the implementation of effective prophylactic strategies.